EVALUATION OF PRESCRIPTION PRACTICES IN THE MEDICINE WARD OF A TERTIARY CARE TEACHING HOSPITAL IN WEST BENGAL: AN OBSERVATIONAL STUDY - SANNIGRAHI, SAIKAT; MONDAL, TANUSREE; BISWAS, RAJARSHI; BISWAS, ARUNAVA; PAUL, SUHRITA (International Journal of Current Pharmaceutical Research, 2026)
Objective: Rational prescribing is crucial for ensuring patient safety, optimizing therapeutic outcomes and minimizing healthcare costs. Irrational prescription practices remain a major concern, particularly the inappropriate use of antimicrobials. Prescription audit serves as a key tool to assess and improve prescribing behaviour, ensuring adherence to standard treatment guidelines. This study aimed to assess the prescribing patterns with special emphasis on the use of antimicrobials and evaluate the rationality of prescriptions in relation to standard treatment guidelines and the principles of essential medicines use. Methods: A cross-sectional, observational study was conducted at Barasat Government Medical College and Hospital over three months. A total of 365 prescriptions were collected through simple random sampling from the medicine wards and hospital records, of which 334 were eligible for analysis. Prescriptions were evaluated using WHO core drug use indicators, and data were analysed descriptively using Microsoft Excel 2021. Results: Generic prescribing was observed in 100% of prescriptions, and 91.3% of drugs were from the National List of Essential Medicines (2022). The average number of drugs per prescription was 5.51, indicating moderate polypharmacy. Antibiotics were prescribed in 0.76 prescriptions reflecting cautious antimicrobial use. Only 35.04% of prescriptions documented a diagnosis, and patient advice was recorded in just 5.39%. The use of injectable formulations (average 4.27/prescription) was relatively high. Conclusion: Prescribing practices largely adhered to rational drug use principles, but areas such as diagnostic documentation, patient counselling, and antimicrobial stewardship require strengthening. Regular audits and training are recommended to further enhance rational pharmacotherapy.